The Influence of Attraction and Facilities on Visitor Satisfaction at Black Stone Beach, Liang Village, Salahutu District, Central Maluku Regency - Ode, Tiansi; Sinay, Fransisca Riconita; Louhenapessy, William George M (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the influence of tourist attractions and facilities on visitor satisfaction at Black Stone Beach, Liang Village, Salahutu District, Central Maluku Regency. Data were collected through a questionnaire distributed to 50 beach visitors and analyzed using multiple linear regression. The results indicate that the variables of tourist attraction and facilities significantly affect visitor satisfaction. The F-test produced an F value of 91.723 with a significance of 0.000, indicating that both independent variables simultaneously affect visitor satisfaction. The t-test results show that the significance values for tourist attraction and facilities are 0.008 and 0.000, respectively, both smaller than 0.05, meaning that both variables significantly influence visitor satisfaction. The normality test shows that the data is normally distributed, while the heteroscedasticity and multicollinearity tests reveal no significant issues with the regression model. Practically, the management of Black Stone Beach is advised to improve the quality of tourist attractions and facilities to enhance visitor satisfaction and encourage an increase in tourist numbers. This finding is expected to provide insights for the management of tourist destinations in further development and contribute to the tourism sector in Maluku Province.